Utilization of Maternity Waiting Home (MWH) to Improve Access to Health Services: Systematic Literature Review - Nuraina Nuraina (Journal of Ners and Midwifery, 2020)
Maternity waiting home (MWH) is a home built in the compound or near to health facilities that provides standard medical and emergency obstetric care services. MWH is considered to be a key strategy to "bridge the geographical gap" in obstetric care between rural areas with poor access to equipped facilities, and urban areas where the services are available. This study aimed to systematically review the utilization of MWH to improve access to health service. The method of finding articles in this study was in the period 2014 to 2018, free full text, human species, and scholarly journals which were then identified using an electronic database from Pubmed, Proquest and Onesearch. Three articles were carried out with thematic analysis to identify the main points. Factors associated with the utilization of MWH included (1) Distance; (2) Complication during pregnancy; and (3) Income. Barrier in the utilization of MWH were (1) Inadequate number of room and postpartum bed; (2) Lack of water and sanitation facilities; and (3) Unavailable electricity. Partnership between health workers in rural facilities, stronger role of stakeholders, and a broader health system, were expected to increase the utilization of MWH.